Sekolah/Madrasah Bertaraf (Branding): Islami, Boarding School, dan Terpadu - Makmur Syukri; Vena Annisa Harahap (Departement of Mathematics Education, 2024)
This article discusses the branding of Islamic, boarding school, and integrated schools/madrasahs as high-quality educational institutions. The research problem is the need to differentiate and compare the three types of high-quality schools/madrasahs and their integration of general and religious education. The research aims to explore the characteristics and educational approaches of Islamic, boarding school, and integrated schools/madrasahs, as well as their role in shaping students' character, independence, and holistic learning. The methodology used is a library research approach, where relevant literature is reviewed and analyzed. The findings show that Islamic schools/madrasahs focus on character formation and spiritual development, boarding schools promote independence and holistic character development, and integrated schools create a holistic learning experience. The implications of this research are the importance of integrating general and religious education, character development, and independence in high-quality Islamic educational institutions.